Adaptive learning in smart cities – The cases of Catania and Helsinki. Issue 1 (May 2017) - Laitinen, Ilpo; Piazza, Roberta; Stenvall, Jari
Our research is a comparative qualitative study. The material has been gathered from the cities of Helsinki and Catania. The target cities showcase varied successes and models of smart cities. In the cities, key people involved in the smart city concept – with different kinds of professional backgrounds – were interviewed, both individually and in teams. All interviewees had at least a basic knowledge of information technology and of organizational learning processes. On the basis of these interviews it has been possible to create an overall picture of learning processes occurring in the organizations involved (universities and local government) and within the smart city programmes produced or still to be developed. We explore how the expertise has been challenged: how the key players of the smart city uphold the concept and promote it.